2020
DOI: 10.1007/s10633-020-09753-4
|View full text |Cite
|
Sign up to set email alerts
|

XEN Gel Stent in the management of primary open-angle glaucoma

Abstract: Purpose To assess the efficacy and safety of the XEN Gel Stent in patients with primary open-angle glaucoma.Materials and methods Twenty eyes of 17 patients (6 males, 11 females) with primary open-angle glaucoma were implanted with XEN Gel Stent. The following data were ascertained in each participant at baseline and at 1, 3, 6, 9 and 12 months following implanting procedure: intraocular pressure, number of anti-glaucoma medications, retinal sensitivity (PS 24/2 w/w), pattern electroretinogram (ISCEV standard)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Among 58 studies that recorded a minimum of 12 months of follow-up, the postoperative weighted mean IOP was 13.6 mm 4,5,12,15,16,[19][20][21][22]72 In all three groups of studies, the weighted mean average number of postoperative medications was less than 1. The results were similar for a second analysis in which studies were clustered in terciles from lowest mean baseline IOP to highest: First 19 studies (range, 15.3-21.0 mm Hg), 4,10,12,21,22,26,32,35,37,41,[46][47][48]50,54,60,61,65,68 second 20 studies (range, 21.1-23.4 mm Hg), 24,28,30,31,33,34,38,40,[42][43][44][45]53,55,57,58,[62][63]…”
Section: Interpretationssupporting
confidence: 58%
See 1 more Smart Citation
“…Among 58 studies that recorded a minimum of 12 months of follow-up, the postoperative weighted mean IOP was 13.6 mm 4,5,12,15,16,[19][20][21][22]72 In all three groups of studies, the weighted mean average number of postoperative medications was less than 1. The results were similar for a second analysis in which studies were clustered in terciles from lowest mean baseline IOP to highest: First 19 studies (range, 15.3-21.0 mm Hg), 4,10,12,21,22,26,32,35,37,41,[46][47][48]50,54,60,61,65,68 second 20 studies (range, 21.1-23.4 mm Hg), 24,28,30,31,33,34,38,40,[42][43][44][45]53,55,57,58,[62][63]…”
Section: Interpretationssupporting
confidence: 58%
“…In 18 prospective studies representing a total of 1591 eyes, a median of 53 eyes (range, 12-221) were followed for a median of 12 months (range, 8-36). 5,10,11,15,21,22,29,31,37,40,43,44,50,54,55,58,63,69 In 41 retrospective studies representing 3111 total eyes, a median of 52 eyes (range, 13-242) were followed for a median of 12 months (range, 6-36). 4,12,16,19,20,[24][25][26][27][28]30,[32][33][34][35][36]38,39,41,42,[45][46][47][48][49][51][52][53][56][57][58][59]…”
Section: Efficacy Outcomesmentioning
confidence: 99%
“…In most studies, the proportion of IOP decreases was >30%. Only 6 studies reported that IOP decreased by <20% (24,30,31,35,49,66). A common feature was found among these studies, which was that the baseline IOP was at a relatively low level of <22 mmHg.…”
Section: Decreasing Iop and Reducing Antiglaucoma Medicationsmentioning
confidence: 99%
“…Cases of stent malposition needed to remove or reimplant of the stent (12). Bleb-related complications comprised bleb leakage (0.68%) and dysesthetic blebs (0.01%) that required sutures (34,53) or revisions (15,35,75).…”
Section: Complicationsmentioning
confidence: 99%
“…1,2 The stent creates an outflow tract for aqueous humor to drain into the subconjunctival space, where it forms a bleb. 1 Mitomycin-C (MMC) is often used in XEN Gel Stent surgery and can be associated with a number of postoperative complications including: hypotony, 3,4 IOP spikes or chronic IOP rise, 3 hyphaema, 4 endophthalmitis, 5 blebitis, 3 persistent anterior chamber inflammation, cystoid macular edema, fibrin formation, 1 fibrosis, 6 and frequent need for postoperative maneuvers. 3 This is, to our knowledge, the first reported case of surgically induced necrotizing scleritis (SINS).…”
mentioning
confidence: 99%